Controlling others and controlling oneself : Social power and emotion suppression - Petkanopoulou, Katerina (Fundación Infancia y Aprendizaje, 2012)
Power is associated with living in reward-rich environments and causes behavioural disinhibition (Keltner, Gruenfeld & Anderson, 2003). Powerful people also have greater freedom of emotional expression (Hecht & LaFrance, 1998). Two studies were conducted with the aim of: a) analyzing the effect of dispositional power on emotion suppression, and b) exploring the simple and interaction effects of dispositional and situational power on emotion suppression. In a first correlational study, the power of individuals was found to be negatively correlated with emotion suppression. In a second experimental study, participants were assigned to a powerful or powerless position and negative emotions were induced with pictures. Participants were asked to suppress their emotions during the presentation of the pictures. Participants' emotion suppression was measured using the suppression subscale of the Emotion Regulation Questionnaire (Gross & John, 2003). Results showed that dispositionally powerless participants suppressed their emotions more than dispositionally powerful participants only when they were assigned to a low power position. These results are discussed.